DEVELOPING STUDENT’S SCIENTIFIC LITERACY BY INCORPORATING LOCAL TERMS AND SOCIOCULTURAL PHENOMENA INTO SCIENCE TEACHING-LEARNING PROCESS - Rizky Purnawati (IKIP Siliwangi, 2024)
The lack of integration between science and culture, students' social-life and science experiences, as well as between students' sociocultural and science world, creates a